2020
DOI: 10.1155/2020/6980918
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Design and Simulation of Creep Test Rig for Full‐Scale Crossarm Structure

Abstract: A simulated model was developed in order to design and simulate the mechanical properties of a cantilever beam creep testing rig for a full-scale size crossarm in transmission towers. Currently, the Malaysian power grid system is implementing several materials, such as Chengal wood, polymeric composite, and galvanised steel, as crossarm structures. However, there is a lack of study regarding the long-term mechanical behaviour of heavy structures in the literature. Hence, this article explains the design develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Due to high cost of carbon fibers, CNTs can be added in small quantities in polymeric composites but exhibit while exhibiting strong mechanical properties [ 249 ]. For instance, the application of CNTs as reinforcements in polymeric composites could establish significantly high mechanical strength and elastic modulus values in comparison other high performance fibers such as Kevlar and carbon [ 143 , 250 , 251 ]. To be specific, their tensile strength and elastic modulus have been recorded at 150 GPa and 1 TPa, respectively, which marks them as tremendously stronger and stiffer, as well as three-to-five times lighter, than steel.…”
Section: Applications and Potential Use Of Carbon Nanotube-reinformentioning
confidence: 99%
“…Due to high cost of carbon fibers, CNTs can be added in small quantities in polymeric composites but exhibit while exhibiting strong mechanical properties [ 249 ]. For instance, the application of CNTs as reinforcements in polymeric composites could establish significantly high mechanical strength and elastic modulus values in comparison other high performance fibers such as Kevlar and carbon [ 143 , 250 , 251 ]. To be specific, their tensile strength and elastic modulus have been recorded at 150 GPa and 1 TPa, respectively, which marks them as tremendously stronger and stiffer, as well as three-to-five times lighter, than steel.…”
Section: Applications and Potential Use Of Carbon Nanotube-reinformentioning
confidence: 99%
“…Studies on the processing effects and natural fibres properties show an improvement in mechanical properties parallel to the National Policy on Industry 4.0 (Industry 4WRD). Natural fibres have sparked great interest among researchers and industry players for their applications in the military [22], automotive [23][24][25][26][27], industrial [28][29][30][31][32][33], furniture [34], civil [35,36], and biomedical fields [37]. It is reported that the natural fibres global production exceeded 105 million metric tons in 2018 [38].…”
Section: Natural Fibrementioning
confidence: 99%
“…Since 1929, the 132 kV cross-arm assembly has been commissioned in the Malaysian electrical grid, using Chengal wood as the structural material [103]. Since it has better mechanical efficiency and excellent quenching of the electric arc [104,105], the wooden cross-arm was selected to be mounted on transmission towers.…”
Section: Pgfrpc Cross-arm In Latticed Transmission Towermentioning
confidence: 99%